2013
DOI: 10.1002/stem.1414
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Expansion of Human outgrowth Endothelial Cells Leads to IL-8-Mediated Replicative Senescence and Impaired Vasoreparative Function

Abstract: Harnessing outgrowth endothelial cells (OECs) for vasoreparative therapy and tissue engineering requires efficient ex vivo expansion. How such expansion impacts on OEC function is largely unknown. In this study, we show that OECs become permanently cell-cycle arrested after ex vivo expansion, which is associated with enlarged cell size, b-galactosidase activity, DNA damage, tumor suppressor pathway activation, and significant transcriptome changes. These senescence hallmarks were coupled with low telomerase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 51 publications
(23 reference statements)
1
36
0
Order By: Relevance
“…growth factors, hypoxia) that are commonly used to study the physiological process such as angiogenic sprouting[34]. Previous comparison of angiogenic ability of ECFCs expanded in medium containing FBS or PL has unraveled that the serum supplement modulates sprouting ability of these cells[35].…”
Section: Discussionmentioning
confidence: 99%
“…growth factors, hypoxia) that are commonly used to study the physiological process such as angiogenic sprouting[34]. Previous comparison of angiogenic ability of ECFCs expanded in medium containing FBS or PL has unraveled that the serum supplement modulates sprouting ability of these cells[35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PSPC effectively renewed the endothelial function of D-gal-treated HUVECs by remarkably we determined the release of inflammatory cytokine interleukin 8 (IL-8) and monocyte chemotactic protein 1 (MCP-1) from HUVECs. Several papershave also demonstrated that these pro-inflammatory factors are crucial facilitators of endothelial senescence[11,40]. The results of the ELISA analysis showed that both the concentration of IL-8 and MCP-1 in cells treated with D-gal for 24 and 48 hours were higher than that in the control cells and PSPC markedly prevented the release of these endothelial function markers in D-gal-treated cells (Fig.…”
mentioning
confidence: 82%
“…Moreover, the release of IL-8 and MCP-1 can be promoted by IL-1β [67,68]. Papers have demonstrated that senescent endothelial cells displayed increased expression of IL-8 and MCP-1, and these cytokines mediated senescence and impaired endothelial function [40,69]. Thus, the levels of IL-8 and MCP-1 can be used as the markers and the cause of endothelial cell senescence.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, when compared to their mature counterparts, progenitor cells, that is, ECFCs/OECs, have been shown to undergo a higher number of population doublings and possess a longer in vitro lifespan [135]. Furthermore, umbilical cord blood-derived ECFCs have an enhanced proliferative potential when compared to those obtained from peripheral blood [109].…”
Section: Endothelial Progenitors and Glycemic Memorymentioning
confidence: 99%